Polymorphisms of genes encoding cytokines predict the risk of high-grade bladder cancer and outcomes of BCG immunotherapy - KRAJEWSKI, WOJCIECH (Cent Eur J Immunol, 2020)
INTRODUCTION: The present study investigated the association of cytokines genes polymorphisms (IL-2, IL-8 and IL-18) and polymorphisms in genes encoding molecules related to the differentiation of Th17 subpopulation (IL-17 and IL-23R) with the risk of bladder cancer (BC) and response to BCG immunotherapy. MATERIAL AND METHODS: Altogether, 175 BC patients treated with BCG due to high-grade non-muscle invasive tumors and 207 healthy individuals were genotyped for the following polymorphisms: IL-17A-197G>A (rs2275913); IL-17F+7488T>C (rs763780); IL-23Rc.309C>A (rs10889677);IL-23Rc.1142G>A (rs11209026); IL-2-330T>G (rs2069762), IL-8-251A>T (rs4073), and IL-18-137G>C (rs187238) using the TaqMan SNP genotyping assays. RESULTS: The IL-23Rc.-309C>A[A] allele was associated with the risk of BC (OR: 1.42, p = 0.03). Moreover, heterozygocities for IL-17A-197G>A[GA] and IL-18-137G>C[GC] increased the risk of BC, as compared to both homozygotes (OR: 1.67, p = 0.01 and OR: 1.84, p = 0.008, respectively). The IL-18-137G>C[GC] heterozygous patients had the highest risk of tumor recurrence and progression, and the worst recurrence-free and progression-free survival. Homozygous IL-17A-197G>A[GG] patients presented the best recurrence-free survival, while IL-17A-197G>A[AA] patients had 1.8-fold higher risk of recurrence. CONCLUSIONS: The present study highlighted the importance of IL-17, IL-18, and IL-23R gene polymorphisms for BC susceptibility and BCG immunotherapy outcomes. It may help to identify appropriate candidates for early radical treatment.